METEOROLOGICAL DATA AT ASUKA STATION, ANTARCTICA IN 1989 - MESHIDA, Shigemi; AZUMA, Nobuhiko; YUKIMATSU, Akira; YAMANOUCHI, Takashi (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper